Dispersal history of Miniopterus fuliginosus bats and their associated viruses in east Asia - Kimprasit, Thachawech; Nunome, Mitsuo; Iida, Keisuke; Murakami, Yoshitaka; Wong, Min-Liang; Wu, Chung-Hsin; Kobayashi, Ryosuke; Hengjan, Yupadee; Takemae, Hitoshi; Yonemitsu, Kenzo; Kuwata, Ryusei; Shimoda, Hiroshi; et al. (PloS one, 2021)
In this study, we examined the role of the eastern bent-winged bat (Miniopterus fuliginosus) in the dispersion of bat adenovirus and bat alphacoronavirus in east Asia, considering their gene flows and divergence times (based on deep-sequencing data), using bat fecal guano samples. Bats in China moved to Jeju Island and/or Taiwan in the last 20,000 years via the Korean Peninsula and/or Japan. The phylogenies of host mitochondrial D-loop DNA was not significantly congruent with those of bat adenovirus (m 2 XY = 0.07, p = 0.08), and bat alphacoronavirus (m 2 XY = 0.48, p = 0.20). We estimate that the first divergence time of bats carrying bat adenovirus in five caves studied (designated as K1, K2, JJ, N2, and F3) occurred approximately 3.17 million years ago. In contrast, the first divergence time of bat adenovirus among bats in the 5 caves was estimated to be approximately 224.32 years ago. The first divergence time of bats in caves CH, JJ, WY, N2, F1, F2, and F3 harboring bat alphacoronavirus was estimated to be 1.59 million years ago. The first divergence time of bat alphacoronavirus among the 7 caves was estimated to be approximately 2,596.92 years ago. The origin of bat adenovirus remains unclear, whereas our findings suggest that bat alphacoronavirus originated in Japan. Surprisingly, bat adenovirus and bat alphacoronavirus appeared to diverge substantially over the last 100 years, even though our gene-flow data indicate that the eastern bent-winged bat serves as an important natural reservoir of both viruses.